The Impact of Gratitude Technique Counseling on Subjective Well Being: A Study on Adolescents in Orphanages - Silvianetri Silvianetri; Irman Irman; Putri Yeni; Isyatur Radhiyah; Alfajri Alfajri; Zubaidah Zubaidah; Syifa Azzahra Silvir (Ta'dib, 2025)
The dominant problem experienced by adolescents in the world today is the low level of subjective well being, which has an impact on learning achievement, mental health, social relationships and quality of life. For this reason, it is necessary to improve the subjective wellbeing of adolescents. One intervention that can be used to improve subjective wellbeing is gratitude technique counseling. The purpose of this study was to examine the effectiveness of gratitude technique counseling on improving adolescents' subjective well being. The approach used is quasi-experimental with posttest only control group design. The study population was adolescents in West Sumatra orphanages who experienced low levels of subjective well being. The research sample was taken randomly with a total of 32 adolescents living in the orphanage, with 16 females and 16 males, consisting of 4 groups. Data were collected using the adolescent subjective well being scale, then the data were analyzed using the Anova difference test through the SPSS computer program. release 20. Furthermore, the post hoc test was carried out through the Tukey test. The results showed that gratitude technique counseling is effective to improve the subjective well being of adolescents living in orphanages with a significance value of .000. It is recommended to practitioners and academics to use gratitude technique counseling to improve the subjective well being of adolescents.